Association of ARHGAP22 gene polymorphisms with the risk of type 2 diabetic retinopathy. (27th July 2017) - Li, Rong; Chen, Peng; Li, Jing; Yan, Mengdan; Li, Jingjie; Li, Shanqu; Zhu, Hongli
Abstract: Background: Little is known about the contribution of ARHGAP22 polymorphism to diabetic retinopathy (DR) risk. We performed a case–control study to investigate the associations between ARHGAP22 and the risk of DR in a Chinese Han population. Methods: A total of 341 patients with type 2 diabetes mellitus (T2DM) were selected. All patients underwent a complete eye examination. Based on this, the patients with T2DM were divided into two subgroups: 188 patients with DR and 153 patients without DR. Five single nucleotide polymorphism (SNPs) were selected and genotyped using the MassARRAY method (Sequenom, San Diego, CA, USA). The odds ratio (OR) and 95% confidence intervals (CIs) were calculated by unconditional logistic regression adjusted for age and sex. Results: Two susceptibility SNPs in ARHGAP22 were found to be associated with an increased risk of DR both before and after the adjustment: rs10491034 under the dominant model (adjusted OR = 0.51, 95% CI = 0.27–0.95, p  = 0.032) and additive model (adjusted OR = 0.47, 95% CI = 0.26–0.84, p  = 0.0098) and rs3844492 under the codominant model (adjusted OR = 3.14, 95% CI = 1.10–9.01, p  = 0.023) and recessive model (adjusted OR = 3.52, 95% CI = 1.26–9.85, p  = 0.011). Conclusions: Our findings reveal a significant association between SNPs in the ARHGAP22 gene and DR risk in a Han Chinese population.